2019
DOI: 10.1101/823096
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

STRIPAK directs PP2A activity toward MAP4K4 to promote oncogenic transformation

Abstract: Alterations involving serine-threonine phosphatase PP2A subunits occur in a range of human cancers and partial loss of PP2A function contributes to cell transformation. Displacement of regulatory B subunits by the SV40 Small T antigen (ST) or mutation/deletion of PP2A subunits alters the abundance and types of PP2A complexes in cells, leading to transformation. Here we show that ST not only displaces common PP2A B subunits but also promotes A-C subunit interactions with alternative B subunits (B''', striatins)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 84 publications
(141 reference statements)
2
10
0
Order By: Relevance
“…STRIPAK is an evolutionarily conserved multiprotein complex that functionally links the phosphatase activity of PP2A to different Ste20-like kinases ( Gordon et al, 2011 ; Goudreault et al, 2009 ; Kim et al, 2020 ; Kück et al, 2019 ; Ribeiro et al, 2010 ; Shi et al, 2016 ). Both enzymatic functions are scaffolded by striatin proteins ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…STRIPAK is an evolutionarily conserved multiprotein complex that functionally links the phosphatase activity of PP2A to different Ste20-like kinases ( Gordon et al, 2011 ; Goudreault et al, 2009 ; Kim et al, 2020 ; Kück et al, 2019 ; Ribeiro et al, 2010 ; Shi et al, 2016 ). Both enzymatic functions are scaffolded by striatin proteins ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study revealed that enteroblasts in Drosophila adult intestine sense the mechanical force generated by food congestion to modulate the Hippo signaling and stem cell activity by regulating the membrane association of Msn and its phosphorylation by Tao-1 ( Jiang, 2018 ; Li et al, 2018 ). Hpo/MST12 and MAP4Ks are negatively regulated by a large protein complex called STRIPAK that brings PP2A to dephosphorylate and inhibit these kinases ( Bae et al, 2017 ; Zheng et al, 2017 ; Kim J.W. et al, 2020 ; Seo et al, 2020 ; Tang et al, 2020 ).…”
Section: Overview Of the Canonical Hippo Signaling Pathwaymentioning
confidence: 99%
“…The cBioPortal for Cancer Genomics (http://cbioportal.org) and The Human Protein Atlas dataset (www.proteinatlas.org) were used to explore, visualize, and analyze multidimensional cancer genomics data. These are open-access resources currently providing data from more than 5,000 tumor samples from 20 cancer studies (18)(19)(20). We also used datasets from The Cancer Genome Atlas (TCGA, https://www.cancer.gov/tcga) (21) and Gynecologic Tissue and Fluid Repository (22).…”
Section: Methodsmentioning
confidence: 99%
“…These resulting ssGSEA scores for individual samples were used for interpreting gene expression profiles using gene sets from the Molecular Signatures Database (MSigDB, www.msigdb.org) (26,27). In addition to the MSigDB gene sets, the YAP gene set used was derived from a previous study (20). To quantify the degree of association, an information-theoretic measure of information coefficient (IC) was calculated and an empirical permutation test for statistical significance calculations carried out against the expression of specific mRNAs (e.g.…”
Section: Methodsmentioning
confidence: 99%